Healthy dietary practices among black South African university students - Karl Peltzer (AOSIS, 2001)
The aim of the study was to investigate five healthy dietary behaviours among black South African University students. Opsomming Die doel van die navorsing was om vyf gesonde dieet gedragstyle van swart Suid-Afrikaanse studente na te vors. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.